A computational study on the kinetics of pyrolysis of isopropyl propionate as a biodiesel model: DFT and ab initio investigation. (1st December 2020) - Shiroudi, Abolfazl; Hirao, Kimihiko; Yoshizawa, Kazunari; Altarawneh, Mohammednoor; Abdel-Rahman, Mohamed A.; El-Meligy, Asmaa B.; El-Nahas, Ahmed M.
Graphical abstract: Highlights: Kinetics of isopropyl propionate (IPP) pyrolysis has conducted at Density functional theory (DFT) and CBS-QB3 methods. Rate constants for IPP decomposition were determined using TST and RRKM theories. The results reveal predominance of propionic acid and propene channel. The studied temperature (563–651 K) is lower than that needed to evaluate competition of the bond energy cleavage reactions. TST approximation breaks down at pressures P  < 10 −4 bar for the most effective reaction. Abstract: This work reports a computational kinetic study on the pyrolysis of isopropyl propionate (IPP) as a biodiesel model using density functional theory (DFT), namely ωB97XD and M06-2X levels. The obtained data are compared with the benchmark CBS-QB3 results. The calculated energy profiles have been supplemented with calculations of rate coefficients and branching ratios over the temperature range 563–651 K and under atmospheric pressure and in the fall-off regime was determined using transition state theory (TST) and statistical Rice-Ramsperger-Kassel-Marcus (RRKM). The obtained results reveal that the formation of propionic acid and propene is the most predominant path both thermodynamically and kinetically. However, production of other species is unlikely to occur except at elevated temperatures, with the hemolytic bond cleavage reactions aren't competitive under the applied temperature range. Comparison with linear methyl and ethyl esters indicates faster reactions for IPP. A good agreement with the available experimental findings has been found. Consistent with higher barrier heights, pressures P  > 10 −4 bar are necessary to achieve the high-pressure (HP) limit.